Improving Access and Quality of Health Care in the United States: Shared Goals Among Patient Advocates - Oehrlein, Elisabeth M.; Harris, Jason; Balch, Alan; Furlong, Pat; Hargis, Eric; Woolley, Mary; Perfetto, Eleanor (The patient : patient-centered outcomes research, 2021)
Patient centricity and patient centeredness broadly refer to any process, program or decision focused on patients in which patients play an active role as meaningfully engaged participants (not simply as study subjects) [2], and patient-centered health care is defined as care that is respectful of and responsive to individual patient preferences, needs, and values in the context of their own social worlds [3]. [...]a Task Force was formed with a multi-stakeholder group of 21 participating organizations. Collecting and sharing patient-centric data (with appropriate privacy protections) should be leveraged to support high-quality health care delivery, research, value assessment, medical product development, and policy efforts. 2.3 Patient-Centricity and Transparency in Health Care Delivery * Principle #6: While one organization or group of stakeholders may not be able to individually achieve implementation of each and every principle, it is valuable for relevant stakeholders to consider which actionable principles can serve as a starting point for collaborative efforts in the short term that can have impact for patients.